Critical Realism and Realist Inquiry in Medical Education. (July 2020) - Ellaway, Rachel H.; Kehoe, Amelia; Illing, Jan
Abstract : Understanding complex interventions, such as in medical education, requires a philosophy of science that can explain how and why things work, or fail to work, in different contexts. Critical realism and its operationalization in the form of realist inquiry provides this explanatory power. Ontologically, critical realism posits that the social world is real, that it exists independent of our knowledge of it, and that it is driven by causal mechanisms. However, unlike postpositivism, a realist epistemological position is that our understanding of the mechanisms that underlay social reality is limited and subjective. Critical realism is focused on understanding the mechanisms that drive social reality even when they are not directly observable. One of the most commonly used methodologies in the critical realist paradigm is realist inquiry, which focuses on the relationships between context, mechanisms, and outcomes. At its core, realist inquiry is concerned with "What works for whom, under what circumstances, how, and why?" To that end, realist inquiry explores the mechanisms that drive social systems and the ways in which these mechanisms work to develop explanatory theories of the phenomena under consideration. Although, compared with other approaches, realist inquiry is relatively new in medical education, the value of realist inquiry is in its ability to model how complex interventions function differently across multiple contexts, explaining what works, how it works, for whom, and in what contexts.